(untitled) (Mustansiria Dental Journal, 2018)
The present in-vitro study was undertaken to compare fracture strength of roots following canal preparation by hand (step-back) and rotary (ProTaper) instrumentation and, further, to determine the direction of fracture lines. Twenty freshly extracted human mandibular premolars were randomly divided into two groups of 10 teeth each. In Group I, canals were prepared with step-back technique using standardized nickel-titanium K-files. In Groups II, canals were prepared with crown-down technique using ProTaper rotary files. After instrumentation, a vertical load was applied by means of a spreader attached to the Instron testing machine and inserted into the canal until fracture occurred. The roots were subsequently examined under a stereomicroscope with 10X magnification to determine the direction of fracture lines. The results were statistically analyzed using paired t-test. The Mean fracture load was 10.420 ± 3.451 kg for K-files and 12.40 ± 4.064 for ProTaper files, the differences between the two groups were not statistically significant (p>0.05). Most of the fracture lines observed were in bucco-lingual direction, followed by proximal and compound fractures. Increased canal taper by ProTaper instrumentation technique did not increase the fracture susceptibility of mandibular premolars any more than conventional step-back K-file preparations and may even increase the fracture resistance.